Análise do uso de embalagens plásticas de insumos em indústria de biscoitos de Arapiraca - AL sob a ótica das práticas Lean e Green - Barbosa, Maria Francilânia Fontes (2023)
One of the challenges facing the food industry as a responsible production process is the reduction and environmentally appropriate disposal of plastic packaging for inputs, given that most raw materials are packaged in plastic materials. Lean and Green thinking can address these challenges, as it is the integration of Lean Manufacturing and Cleaner Production practices to reduce waste and environmental impacts in the life cycle stages of products and processes. This research sought to analyze the use of plastic packaging for cookie manufacturing inputs in a small food industry in the city of Arapiraca, Alagoas-Brazil, based on Lean and Green practices, with a view to proposing opportunities for environmental improvement in the production process. To this end, bibliographical and documentary research was carried out to identify Lean and Green practices; a characterization of plastic packaging and the environmental aspects and impacts of plastic materials in the cookie production process was carried out, and a case study of an industry in Alagoas was analyzed. As a result, 21 Lean and Green practices were found that can be applied to implement lean and green thinking in small production groups; and among them, 7 practices/tools were identified that the case study industry can apply as opportunities for environmental improvement. These are: applying the 3Rs Reduce, Reuse, Recycle to plastic packaging, selecting suppliers based on environmental criteria, reducing packaging with bulk purchases, life cycle assessment (LCA), reverse logistics for plastic packaging in partnership with manufacturers and suppliers, replacing raw materials purchased in plastic packaging with more biodegradable packaging and raising staff awareness and guidance on the environmental impacts of plastic packaging. As for disposal, 62.5% of plastic packaging is sent to the landfill in the Agreste Alagoano region and 37.5% is sold. It was found that the main challenges for small companies in implementing Lean and Green practices are access to financial resources and the lack of training for managers and employees.